2018
DOI: 10.1093/ibd/izy058
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factor Analysis of Thromboembolic Events in East Asian Patients With Inflammatory Bowel Disease, a Multinational Collaborative Study

Abstract: East Asian IBD patients carry a 2-fold increased risk of VTE than the general population. The incidence of VTE in the East Asian IBD patients is still lower than that in Western countries. Therefore, close monitoring rather than routine prophylaxis of VTE in East Asian IBD patients is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
55
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 37 publications
12
55
1
1
Order By: Relevance
“…in the OLE study were those who completed OCTAVE Induction 1 and 2 without clinical response, and those who completed OCTAVE Sustain but were not in remission, or were early withdrawals due to treatment failure in OCTAVE Sustain. IRs for DVT and PE events with tofacitinib were comparable with those reported for patients with UC …”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…in the OLE study were those who completed OCTAVE Induction 1 and 2 without clinical response, and those who completed OCTAVE Sustain but were not in remission, or were early withdrawals due to treatment failure in OCTAVE Sustain. IRs for DVT and PE events with tofacitinib were comparable with those reported for patients with UC …”
Section: Discussionsupporting
confidence: 70%
“…e Severities were assessed as moderate (2) and severe (2). 24,26 The present post hoc analysis provides information for physicians regarding the incidence of DVT and PE in patients with UC who were treated with tofacitinib, but is limited by small sample size and drug exposure. Further studies of venous thromboembolism in patients with UC treated with tofacitinib are needed.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Our multinational collaborative study enrolled 2,562 hospitalized IBD patients from Korea, Japan and Taiwan showed the average incidence of VTE was 0.72–1.38 per 1,000 persons per year in East-Asian patients with IBD. 18 In Western patients with IBD, the overall incidence of VTE has been determined to be 2.4–2.6 per 1,000 persons per year. 10 11 Because of the relatively low incidence of VTE, the benefits of pharmacological prophylaxis are expected to be small in Asian patients with IBD.…”
mentioning
confidence: 99%
“…A VTE prevalence of 2.3-25.3% in hospitalized patients with psychiatric disorders does not seem high compared to the VTE prevalence in hospitalized patients with nonpsychiatric disorders. [2][3][4] The prevalence of VTE has been reported at 0.5-58% in hospitalized non postsurgical patients with nonpsychiatric disorders, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and at 4.8-24.4% in those without VTE symptoms. 14,17,19,24 Given the recent increase in the number of people requiring hospitalization for VTE, clarifying the prevalence of VTE in hospitalized patients with psychiatric disorders such as depression is of academic as well as of clinical value.…”
Section: Introductionmentioning
confidence: 99%